Fully endoscopic neurosurgery using a two-handed technique for cerebellopontine angle tumors via the retrosigmoid approach - Xie, Zhengxing; Zhuang, Yan; Liu, Jieping (Frontiers in Oncology, 2024)
BackgroundSurgery for tumors in the cerebellopontine angle is always a significant challenge due to the densely packed neurovascular structures, the narrow deep location, and the complex relationship between the lesions and surrounding neurovascular structures. Recently, great attention has been given to the neuroendoscope for its exclusive advantages, which have added a new dimension to many classical microscopic surgeries. However, the feasibility and advisability of fully endoscopic neurosurgery for cerebellopontine angle tumors remain to be further evaluated.MethodsWe retrospectively collected the clinical outcomes and endoscopic surgical experience of 12 patients with tumors in the cerebellopontine angle (CPA) from January 2022 to April 2024 in our department. We analyzed patients’ records, radiological neuroimaging, tumor-related variables, surgical procedures, and postoperative outcomes in detail. All patients were regularly followed up with neurological examinations and magnetic resonance imaging (MRI)/computed tomography (CT).ResultsThe pathology of the series included five cases of acoustic neuroma, six cases of meningioma, and one case of teratoma. The mean largest diameter of the lesion was 29.5 mm ±8.5 mm. Headache, hearing loss, and dizziness were the top three most common symptoms. All tumors were resected using the hand technique. No hemorrhage, cerebrospinal fluid leaks, or intracranial infections occurred. All patients with meningioma achieved Simpson grade II resection, and the remaining tumors underwent gross total resection, confirmed by both intraoperative and postoperative imaging. Overall, 91.7% of patients maintained normal facial nerve function postoperatively (HB1). One patient with acoustic neuroma experienced transient facial paralysis after surgery (HB2), which resolved during follow-up at 3 months postoperation. Clinical symptoms of all the other patients were resolved or ameliorated after surgery, with no new neurological deficits. The Karnofsky Performance Scale (KPS) scores remained unchanged or improved for all patients postoperatively.ConclusionsWith the accumulation of experience and technological progress, the fully endoscopic retrosigmoid approach could enable safe and effective resection of cerebellopontine angle tumors, providing a panoramic view and illumination of deep-seated structures.